Scientific capital in public health: an analysis inspired by Homo academicus and its sources - Deslandes, Suely; Maksud, Ivia (Saúde e Sociedade, 2019)
A social space for the production of knowledge and practices, public health (PH) is recognized by its researchers as a “field,” in accordance with Pierre Bourdieu’s basilar definition. The scientific field is a social microcosm with its own laws, in which the agents and institutions that produce, reproduce and disseminate science are inscribed. Based on Bourdieu’s work Homo academicus, this essay proposes a set of indicators to compose an analysis matrix for the distribution of prestige capital, notoriety, and academic power in the Brazilian PH scientific field. These indicators were adapted to the nationally available data, so as to ensure the feasibility of their application. We made use of official documents that define the desirable productivity criteria for the performance of permanent professors in graduate courses and the eligibility criteria for research productivity scholarships. The proposed matrix allows for a mappingof capitaldistributionamongresearchers, according to their field or institution of origin. Such an analytical exercise on the distribution of political capital, prestige and notoriety in the PH scientific field helps us better understand the field’s dynamics when it comes to the production of academic distinction. This kind of analysis invites us, in Bourdieu’s words, to a “collective self-analysis.”